ISU PEREMPUAN SEBAGAI MASALAH SOSIAL KAJIAN PERSPEKTIF AJARAN SOSIAL GEREJA - Eddy Kristiyanto (Studia Philosophica et Theologica, 2005)
Issues on women in the recent time actually are very distinctive and significant. It is quite prominent that this issue belongs to the social question. In account of the concept that the terminology of “social” means it includes the interests, policis, needs, conscientisation of many sides. Speaking of woman means speaking of life, family, education, participation, human right, deliberation, etc. It is interesting that along its revelation, the Catholic social doctrine did not occupy sufficiently on this issue. Traditionally discusing, the major Catholic sosial doctine puts that issue on the question of man and family at all and generally, indicating that the nature of every woman is arround in the family busines. For that reason, one can pick up the impression that the doctrine does not care on the question yet. In this doctrine, however, issue on women more and more precious. From this point of view, the social doctrine also kept the evolution minded. Woman as the image of God begins the practical implications.